2013
DOI: 10.1002/pssa.201329040
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional TEM imaging of β-Ga2 O3 thin films formed on c -plane and a -plane sapphire substrates

Abstract: We investigated in detail the microstructure of 2true‾01‐oriented β‐Ga2O3 thin films on sapphire substrates by transmission electron microscopy (TEM) and electron diffraction. Cross‐sectional TEM images of the films on (001) c‐plane and (110) a‐plane sapphire substrates are composed of four types of regions with different atomic arrangements. The consideration based on the crystal orientation of β‐Ga2O3 showed that the type of TEM images corresponds to the projection direction caused by the rotation of the β‐G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
8
13
0
Order By: Relevance
“…X‐ray pole figure diffraction measurements revealed that crystals of (−201)‐oriented β‐Ga 2 O 3 were rotated every 60° and that six types of β‐Ga 2 O 3 crystals formed on the substrate. These results were also confirmed from cross‐sectional TEM images of (−201)‐oriented β‐Ga 2 O 3 crystals on (001) c ‐plane and (110) a ‐plane sapphire substrates . In particular, we found that (−201)‐oriented β‐Ga 2 O 3 crystals on (110) a ‐plane sapphire substrates consist of six types of β‐Ga 2 O 3 crystals rotated every 60° from the [0‐10] or [‐110] directions; we explained the orientation using oxygen atomic arrangements.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…X‐ray pole figure diffraction measurements revealed that crystals of (−201)‐oriented β‐Ga 2 O 3 were rotated every 60° and that six types of β‐Ga 2 O 3 crystals formed on the substrate. These results were also confirmed from cross‐sectional TEM images of (−201)‐oriented β‐Ga 2 O 3 crystals on (001) c ‐plane and (110) a ‐plane sapphire substrates . In particular, we found that (−201)‐oriented β‐Ga 2 O 3 crystals on (110) a ‐plane sapphire substrates consist of six types of β‐Ga 2 O 3 crystals rotated every 60° from the [0‐10] or [‐110] directions; we explained the orientation using oxygen atomic arrangements.…”
Section: Introductionsupporting
confidence: 83%
“…Gallium was then evaporated using a heater. The preparation and crystal orientation of β‐Ga 2 O 3 layers on c ‐plane and a ‐plane sapphire substrates by this method have been previously reported in detail .…”
Section: Methodsmentioning
confidence: 99%
“…The X‐ray pole figure diffraction measurements revealed that crystals of (−201)‐oriented β‐Ga 2 O 3 have a sixfold crystal domain structure on both the (001) c ‐plane sapphire substrate and the (110) a ‐plane sapphire substrate. These results were confirmed by cross‐sectional TEM images .…”
Section: Introductionsupporting
confidence: 70%
“…Precise transmission electron microscopy and electron diffraction analyses have been recently carried out on (201) oriented β-Ga 2 O 3 films grown by Ga evaporation in oxygen plasma on c-cut sapphire substrates [37]. The results show that various in-plane orientations of the film on the substrate can exist, i.e., instead of a fixed 60°rotation between all the six variants, values of the rotation equal to 58.2 and 63.6°have been reported [37]. Such values are in agreement with the two distinct in-plane orientations described in Fig.…”
Section: Results and Interpretationsmentioning
confidence: 99%